Insentif Pada Kebijakan Dividen: Apa Yang Kita Ketahui Dan Apa Selanjutnya? Tinjauan Systematic Literature - Shindy Dwita Nuansari; Meme Rukkmini (LP3M Universitas Kadiri, 2023)
Companies are competing to increase the value of the company to improve the welfare of shareholders, one of which is by determining the best dividend policy. This study aims to present a systematic review of the catering dividend by examining publication trends, journal rankings and citation profiles, factors, and their interactions. This study also attempts to propose a conceptual model based on the identification of variables in a systematic review study. This research uses systematic review analysis by searching for article sources in the Scopus database. A total of 42 articles published from 2004 – 2022 were selected. This study uses systematic data to reveal trends in dividend catering studies with a qualitative inductive analysis to determine relevant themes by classifying and discussing potential future research. The results of the study show that the topic of catering dividends has been widely used by various studies on dividend policy. Interestingly, this study finds a limited focus on the ASEAN region. In addition, research on catering dividends is dominated by fundamental observations that influence investors' evaluation of paying firms. In addition, it is necessary to observe further regarding other antecedent factors such as the characteristics of the controlling shareholders and the majority gender of investors. Furthermore, the consequences can be studied broadly, for example the impact on the company's capital structure. This study provides future directions for research on dividend catering. In addition, this study maps the antecedents, processes, and consequences of catering dividends. This study reveals dividend catering study trends, journal rankings and citation profiles, factors, and their interactions studied. It also proposes a conceptual model based on the identification of variables in previous research to provide directions for future research on dividend catering. Keyword : Incentives Catering, Dividend Policy and Systematic Review.